Book Reviews. - CHUNG, HILARY; COUCHMAN, SOPHIE; DUBOIS, THOMAS; LEE, MABEL; PENNY, BENJAMIN; BAYARI, CELAL; DOLLASE, HIROMI T.; GRAINGER, RICHARD; OKANO, KAORI; ROBERSON, JAMES E.; CHACKO, PRIYA; ASPINALL, EDWARD; et al. (Asian Studies Review, 2007)
The article reviews several books including "Hedda Morrison's Hong Kong: Photographs and Impressions, 1946-47," by Edward Stokes, "Buddhism, War, and Nationalism: Chinese Monks in the Struggle Against Japanese Aggressions, 1931-1945," by Xue Yu, and "Turning Pages: Reading and Writing Women's Magazines in Interwar Japan," by Sarah Frederick.